Anamnesis: Makna Teologis Berdasarkan Sudut Pandang Alexander Schmemann dan John Calvin sebagai Diskusi Oikumenis - Lunardi, Jeconiah (STT Reformed Injili Internasional, 2025)
This study analyses the concept of anamnesis in the Lord's Supper based on the perspectives of John Calvin from the Reformed tradition and Alexander Schmemann from the Eastern Orthodox tradition. Both theologians agree that anamnesis is not merely a cognitive remembrance but a divine act of the Triune God that deepens the believers' communion with Christ. However, differences arise in their interpretations of telos, the expression of Christ’s sacrificial love, and the scope of anamnesis, where Schmemann emphasizes the manifestation of the Kingdom of God in liturgy, while Calvin focuses on the justification and sanctification of believers. This study contributes to the ecumenical dialogue by offering a synthesis that values both traditions without compromising theological integrity. Thus, it enriches the understanding of anamnesis as a theological reality that brings forth God's salvific work in the Lord’s Supper and directs believers toward eschatological fulfilment.